THE ANALYSIS THE EFFECT OF MACROECONOMIC FACTORS ON INDONESIA 10-YEAR GOVERNMENT BOND YIELD - Juliana Pratiwi, Chyntia; H. Mustafa, Matrodji (Dinasti Publisher, 2021)
The purpose of this research is to analyze macroeconomics, namely Inflation, Gross Domestic Product, Exchange Rates, Interest Rates and Sovereign Risk to Indonesia 10-Year Government Bond Yield. The population in this study were all government bond yield tenors of the benchmark series for the period 2017 to 2019. The type of research used in this study is causal associative research. The research sample is Indonesian government bonds with a tenor of 10 years. The sample amounted to 36 data. The data analysis technique used multiple regression analysis method. The results showed that inflation and Gross Domestic Product have no effect on the Indonesia 10-Year Government Bond Yield. Exchange Rates, Interest Rates and Sovereign Risk have a positive and significant effect on the Indonesia 10-Year Government Bond Yield.